In vivo analgesic, antipyretic, and anti-inflammatory potential in Swiss albino mice and in vitro thrombolytic activity of hydroalcoholic extract from Litsea glutinosaleaves - Rumpa Bhowmick; Md Shahid Sarwa; Syed Masudur Rahman Dewan; Abhijit Das; Binayok Das; Mir Muhammad Nasir Uddin; Md Siddiqul Islam; Mohammad Safiqul Islam (Biological Research, 2014)
BACKGROUND: The study was conducted to evaluate the in vitro thrombolytic activity, and in vivo analgesic, anti-inflammatory and antipyretic potentials of different hydrocarbon soluble extracts of Litsea glutinosaleaves for the first time widely used in the folkloric treatments in Bangladesh. This work aimed to create new insights on the fundamental mechanisms of the plant extracts involved in these activities. RESULTS: In thrombolytic activity assay, a significant clot disruption was observed at dose of 1 mg/mL for each of the extracts (volume 100 μL) when compared to the standard drug streptokinase. The n-hexane, ethyl acetate, chloroform, and crude methanolic extracts showed 32.23 ± 0.26, 37.67 ± 1.31, 43.13 ± 0.85, and 46.78 ± 0.9% clot lysis, respectively, whereas the positive control streptokinase showed 93.35 ± 0.35% disruption at the dose of 30,000 I.U. In hot plate method, the highest pain inhibitory activity was found at a dose of 500 mg/kg of crude extract (15.54 ± 0.37 sec) which differed significantly (P <0.01 and P <0.001) with that of the standard drug ketorolac (16.38 ± 0.27 sec). In acetic acid induced writhing test, the crude methanolic extract showed significant (P <0.01 and P <0.001) analgesic potential at doses 250 and 500 mg/kg body weight (45.98 and 56.32% inhibition, respectively), where ketorolac showed 64.36% inhibition. In anti-inflammatory activity test, the crude methanolic extract showed significant (P <0.001) potential at doses 250 and 500 mg/kg body weight (1.51 ± 0.04 and 1.47 ± 0.03 mm paw edema, respectively), where ketorolac showed 1.64 ± 0.05 mm edema after 3 h of carrageenan injection. In antipyretic activity assay, the crude extract showed notable reduction in body temperature (32.78 ± 0.46°C) at dose of 500 mg/kg-body weight, when the standard (at dose 150 mg/kg-body weight) exerted 33.32 ± 0.67°C temperature after 3 h of administration. CONCLUSIONS: Our results yield that the crude hydroalcoholic extract has better effects than the other in all trials. In the context, it can be said that the leaves of L. glutinosa possess remarkable pharmacological effects, and justify its traditional use as analgesic, antipyretic, anti-inflammatory, and thrombolytic agent.